Toll-like Receptors - Rezaei, Nima (IntechOpen, 2020)
Toll-like receptors (TLRs) are pattern recognition receptors that allow innate immunity to protect our body against invading pathogens. They are alsoregulators of adaptive immunity. The human TLR was discovered quite recently, but its functional significance is known worldwide and today TLR agonists have been approved for use in humans. This book provides an overview of TLRs and their role in parasitic infections and neurodegenerative diseases. It is hoped that it will encourage readers to seek out the latest developments in TLRs.